METODE ISTINBAT HUKUM MUHAMMAD ABU ZAHRAH DALAM PENCATATAN HUKUM PERKAWINAN PERSPEKTIF SOSIOLOGI HUKUM DI INDONESIA - Pratama, Agung; Miftahul Huda; Salimul Jihad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines Muhammad Abu Zahrah's method of legal istinbat in relation to marriage registration in Indonesia from the perspective of the sociology of law. The research is motivated by the importance of marriage registration as a form of legal protection for family rights within the context of modern social development. In classical Islamic law, marriage registration is neither a pillar nor a condition for the validity of marriage; however, within the Indonesian legal system, marriage registration is mandatory to ensure legal certainty and social order. This study employs a library research method using normative and sociological approaches. Data were collected from books, academic journals, statutory regulations, and previous studies related to Muhammad Abu Zahrah’s legal reasoning methodology, marriage registration, maqāṣid al-sharī‘ah, and qawā‘id fiqhiyyah. The findings reveal that Abu Zahrah’s method of legal istinbat is dynamic and oriented toward public welfare (maṣlaḥah). He considers the Qur’an, Hadith, ijmā‘, qiyās, and maṣlaḥah as essential foundations in the formulation of Islamic law. The relevance of Abu Zahrah’s thought to marriage registration in Indonesia can be seen through the application of maṣlaḥah and maqāṣid al-sharī‘ah, which aim to preserve religion (ḥifẓ al-dīn), intellect (ḥifẓ al-‘aql), lineage (ḥifẓ al-nasl), and property (ḥifẓ al-māl). Furthermore, the implementation of legal maxims (qawā‘id fiqhiyyah), such as dar’ al-mafāsid muqaddam ‘alā jalb al-maṣāliḥ (preventing harm takes precedence over attaining benefits) and taṣarruf al-imām ‘alā al-ra‘iyyah manūṭun bi al-maṣlaḥah (the policies of a ruler toward the people must be based on public welfare), demonstrates that the obligation of marriage registration possesses a strong foundation of public interest within Islamic law. Therefore, marriage registration in Indonesia may be understood as a form of modern legal ijtihād that is consistent with the objectives of Islamic law and the social needs of society in promoting legal protection, justice, and social order.